Tillage, Glyphosate and Beneficial Arbuscular Mycorrhizal Fungi: Optimising Crop Management for Plant–Fungal Symbiosis - Thomas I. Wilkes (Agriculture, 2020)
Zero till cropping systems typically apply broad-spectrum herbicides such as glyphosate as an alternative weed control strategy to the physical inversion of the soil provided by cultivation. Glyphosate targets 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase in plants. There is growing evidence that this may have a detrimental impact on non-target organisms such as those present in the soil microbiome. Species of commercial importance, such as arbuscular mycorrhizal (AM) fungi that form a symbiotic relationship with plant roots are an important example. This study investigates the impact of soil cultivation and glyphosate application associated with conventional tillage (CT) and zero tillage (ZT) respectively on AM fungi populations under field and glasshouse conditions. Topsoil (<10 cm) was extracted from CT and ZT fields cropped with winter wheat, plus non-cropped control plots within the same field boundary, throughout the cropping year. Glyphosate was applied in glasshouse experiments at rates between 0 and 350 g L−1. Ergosterol, an indicator of fungal biomass, was measured using high performance liquid chromatography before and after glyphosate application. Fungal root arbuscules, an indicator of AM fungi–root symbiosis, were quantified from the roots of wheat plants. Under glasshouse conditions root arbuscules were consistently higher in wheat grown in ZT field extracted soils (P = 0.01) compared to CT. Glyphosate application however inhibited fungal biomass in both the ZT (P < 0.00001) and CT (P < 0.001) treatments. In the absence of glyphosate, the number of stained root arbuscules increased significantly. Ergosterol levels, used as a proxy for fungal biomass, remained lower in the soil post glyphosate application. The results suggest that CT has a greater negative impact on AM fungal growth than ZT and glyphosate, but that glyphosate is also detrimental to AM fungal growth and hinders subsequent population recovery.